Boraalkenes Made by a Hydroboration Route: Cycloaddition and B=C Bond Cleavage Reactions. (20th December 2022) - Jie, Xiaoming; Chen, Chaohuang; Daniliuc, Constantin G.; Kehr, Gerald; Erker, Gerhard
Abstract: Hydroboration of styrene or vinylcyclohexane with the IMes(C6 F5 )BH + cation followed by deprotonation provided a convenient synthetic entry to the [B]=CHCH2 R boraalkenes 9 a and 9 b . The in situ generated IMes(SCN)BH + system reacted similarly with 1, 1‐diphenylethene followed by deprotonation to give the isothiocyanato substituted boraalkene 9 c . The boraalkenes underwent [2+2] cycloaddition reactions with a small series of heterocumulenes to give the respective four‐membered heterocycles. The [B]=CHCH2 R+CO2 cycloadducts 13 a and 13 b added the borane HB(C6 F5 )2 with cleavage of the central B−C σ‐bond. CS2 underwent an unusual reaction with the boraalkenes, namely insertion into the B=C bond with formation of the borylated dithioketene acetal under complete rupture of the strong B=C double bond. The intermediate dithiobora‐β‐lactone type intermediate was isolated in the case of the isothiocyanato‐boraalkene reaction and characterized by X‐ray diffraction. Abstract : Alkene hydroboration by the in situ generated IMes(X)BH + cations followed by deprotonation gave the neutral boraalkenes. They underwent [2+2] cycloaddition with a variety of heterocumulenes among them carbon dioxide and carbon disulfide. A two‐step reaction sequence led to the formal CS2 insertion product with complete rupture of the B=C double bond. A boraalkene/CO2 cycloaddition product opened its core B−C bond upon treatment with HB(C6 F5 )2 .